KONSEP PENDIDIKAN SEKOLAH ISLAM TERPADU - Ismael, Fauzan; Iswantir, Iswantir (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of writing this article is to look at the concept of integrated Islamic education in Indonesia. Integrated Islamic schools emerged as a form of response to the dissatisfaction of Islamic movement activists with the national education system in Indonesia. The national education system is considered to perpetuate dualism in the management of education between religious and general education. Therefore, an alternative educational institution model is needed that is able to eliminate the existence of dichotomous educational practices. The conclusion results can be understood that the Integrated Islamic School is an integral part of the national education system. Its relationship with the space of Islamic education. Islamic educational institutions consisting of pesantren , madrasas and public schools are slowly starting to change. Integrated Islamic boarding schools are likely to emerge as an alternative solution to Islam. Learn about the agitation of urban Muslim communities in cities for an Islamic institution that stands out. The integration of Islamic schools was born as an answer to various demands and problems of the local people and it is the dream and hope of the government to combine these two schools into a unitary spirit that combines general education with Islamic education.